1996
DOI: 10.1002/(sici)1097-0142(19960115)77:2<402::aid-cncr25>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of octreotide in the treatment of metastatic neuroendocrine tumors: A study by the Italian Trials in Medical Oncology group

Abstract: In terms of tumor regression, octreotide is disappointing (partial response: 3%); symptomatic response and biochemical control are satisfactory. These data confirm that somatostatin analogues are comparable to interferons in the treatment of carcinoid syndrome, although other efforts are necessary to control tumor regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
2
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(106 citation statements)
references
References 23 publications
8
89
2
7
Order By: Relevance
“…Six studies in the following decade showed that 15%-86% of patients with advanced NETs achieved stable disease with octreotide SC (Table 1) [22,23,26,28,29,31]. After the introduction of octreotide LAR, several more studies reinforced the results observed with the SC formulation [27, 30, 32, 34 -37].…”
Section: Octreotidesupporting
confidence: 74%
“…Six studies in the following decade showed that 15%-86% of patients with advanced NETs achieved stable disease with octreotide SC (Table 1) [22,23,26,28,29,31]. After the introduction of octreotide LAR, several more studies reinforced the results observed with the SC formulation [27, 30, 32, 34 -37].…”
Section: Octreotidesupporting
confidence: 74%
“…A long-acting depot form of octreotide (octreotide LAR), which can be administered on a monthly basis, has gained popularity. Octreotide therapy results in remission or stabilization of tumor markers, such as serotonin and chromogranin A, in approximately 60% to 70% of patients [27,28].…”
Section: Somatostatin Analogssupporting
confidence: 88%
“…By contrast, SSTR4 up-regulates the MAPK/ERK1/2 pathway leading to proliferative activity. SSTRs are also related to multiple secondary effectors such as adenylyl cyclase and protein kinase A (6) and ion channel regulation such as K C channel, voltagedependent Ca 2C channel, Na C /H C exchanger or AMPA/ Kainate glutamate channels (7) (Fig. 2).…”
Section: Molecular Biology and The Rationale Behind The Use Of Ssas Amentioning
confidence: 99%